2020
DOI: 10.1016/j.cmet.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Anti-diabetic, Orally Available Small Molecule that Regulates TXNIP Expression and Glucagon Action

Abstract: Diabetes is characterized by hyperglycemia, loss of functional islet beta cell mass, deficiency of glucoselowering insulin, and persistent alpha cell secretion of gluconeogenic glucagon. Still, no therapies that target these underlying processes are available. We therefore performed high-throughput screening of 300,000 compounds and extensive medicinal chemistry optimization and here report the discovery of SRI-37330, an orally bioavailable, non-toxic small molecule, which effectively rescued mice from strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…Independent of redox regulation, TXNIP also functions as a regulator of glucose metabolism [ 82 ]. Finally, the recent report that TXNIP levels are increased in diabetes is consistent with the enhanced susceptibility of LS patients to develop type 2 diabetes mellitus [ 83 ].…”
Section: Identification Of Thioredoxin-interacting Protein As a Nesupporting
confidence: 64%
“…Independent of redox regulation, TXNIP also functions as a regulator of glucose metabolism [ 82 ]. Finally, the recent report that TXNIP levels are increased in diabetes is consistent with the enhanced susceptibility of LS patients to develop type 2 diabetes mellitus [ 83 ].…”
Section: Identification Of Thioredoxin-interacting Protein As a Nesupporting
confidence: 64%
“…Thielen L.A. et al recently identified a small-molecule inhibitor, SRI-37330, that effectively suppresses TXNIP expression in rats, mice, and human pancreatic islets. In addition, treatment with SRI-37330 reduces glucagon secretion and hepatic glucose production and reverses streptozotocin-induced diabetes [ 154 ]. Nonetheless, further studies are warranted to determine the therapeutic window for clinical trials.…”
Section: Txnip Is a Potential Therapeutic Targetmentioning
confidence: 99%
“…Interestingly, after a screen of more than 300,000 molecules, Thielen and co-workers recently identified a compound that downregulates TxNIP in mouse and human pancreatic islets. When given orally to mice, this small molecule (SRI-37330) lowered serum levels of glucagon, prevented fatty liver, and inhibited glucose production by the liver ( Thielen et al., 2020 ). In this context, TxNIP continues to generate significant interest as a potential therapeutic target for the management of diabetes and other metabolic disorders ( Yoshihara, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, owing to its diverse array of functions in glucose and lipid metabolism in several cell types, TxNIP has been considered as a novel candidate drug target for type 2 diabetes ( Thielen and Shalev, 2018 ). Interestingly, a study recently identified a novel anti-diabetic small molecule SRI-37330 that inhibits TxNIP expression and signaling in mouse and human islets ( Thielen et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%